Point Prevalence Survey Of Antimicrobial Use And Determinants Of Antimicrobial Resistance In Selected Healthcare Settings In Punjab, Pakistan - Zikria, Zikria (2020)
The threat of antimicrobial resistance (AMR) has appeared as a global health crisis. World Health Organization (WHO) has launched a Global Action Plan (GAP) to tackle AMR, which was endorsed by all countries, including Pakistan. Despite the National Action Plan (NAP) on AMR, no significant measures have been taken so far in Pakistan. Thus, this study aims to address this by assessing patterns of antimicrobial prescribing and susceptibility, healthcare-associated infection (HAI) rates, extent of antimicrobial stewardship programs (ASPs), determinants of AMR and patterns of antimicrobial prescribing and dispensing among physicians and pharmacists. In line with the recent NAP on AMR, the first time such a comprehensive study has been undertaken in Pakistan. Mixed methods research was used, including point prevalence surveys (PPS) and extensive face-to-face interviews. Out of 1954 patients analyzed in PPS, 1516 (77.6%, range 50.9%-100%) were treated with antimicrobials, with the most commonly prescribed antimicrobial was ceftriaxone (35.0%).